Examining the role of motivation in shaping future primary school teachers’ professional competence in Kazakhstan - Kereibaeva, Anar; Zhailauova, Manat; Baimaganbetova, Zhuldyzai; Abuova, Ainagul; Utegenov, Zhetkergen (Journal of Education and e-Learning Research, 2024)
The issue of developing the professional competence of teachers is one of the priorities in the Kazakhstani education system. One of the most significant challenges in the context of improving abilities is increasing students’ motivation. This study aims to examine the role of motivation in shaping future primary school teachers’ professional competence. The methods of multivariate correlation analysis, a method for finding structure diagrams of motives and their integral subsystems with their subsequent analysis were used to conduct the study. The research was conducted at the Korkyt Ata Kyzylorda University (Kyzylorda, Kazakhstan). A sample of 57 participants was used for the study. The majority of respondents were female (92.36%) and male (7.64%). According to the study, it has been found that the main reason for studying among students is to receive vocational training in order to find a good and well-paid job which provides the opportunity to use personal abilities and receive higher education in their specialty. Following the findings of this study, practical recommendations are offered to increase student motivation as a factor in developing professional competence. The developed assessment-criteria diagnostic tools can be used in pedagogical monitoring in universities and in advanced training courses for teachers.